Development and evaluation of a fish feed mixture containing the probiotic Lactiplantibacillus plantarum prepared using an innovative pellet coating method - Chomová, Natália; Pavloková, Sylvie; Sondorová, Miriam; Mudroňová, Dagmar; Fečkaninová, Adriána; Popelka, Peter; Koščová, Jana; Žitňan, Rudolf; Franc, Aleš (Frontiers in Veterinary Science, 2023)
Introduction Due to the intensification of fish farming and the associated spread of antimicrobial resistance among animals and humans, it is necessary to discover new alternatives in the therapy and prophylaxis of diseases. Probiotics appear to be promising candidates because of their ability to stimulate immune responses and suppress the growth of pathogens. Methods The aim of this study was to prepare fish feed mixtures with various compositions and, based on their physical characteristics (sphericity, flow rate, density, hardness, friability, and loss on drying), choose the most suitable one for coating with the selected probiotic strain Lactobacillus plantarum R2 Biocenol™ CCM 8674 (new nom. Lactiplantibacillus plantarum). The probiotic strain was examined through sequence analysis for the presence of plantaricin- related genes. An invented coating technology based on a dry coating with colloidal silica followed by starch hydrogel containing L. plantarum was applied to pellets and tested for the viability of probiotics during an 11-month period at different temperatures (4°C and 22°C). The release kinetics of probiotics in artificial gastric juice and in water (pH = 2 and pH = 7) were also determined. Chemical and nutritional analyses were conducted for comparison of the quality of the control and coated pellets. Results and discussion The results showed a gradual and sufficient release of probiotics for a 24-hour period, from 104 CFU at 10 mi up to 106 at the end of measurement in both environments. The number of living probiotic bacteria was stable during the whole storage period at 4°C (108), and no significant decrease in living probiotic bacteria was observed. Sanger sequencing revealed the presence of plantaricin A and plantaricin EF. Chemical analysis revealed an increase in multiple nutrients compared to the uncoated cores. These findings disclose that the invented coating method with a selected probiotic strain improved nutrient composition and did not worsen any of the physical characteristics of pellets. Applied probiotics are also gradually released into the environment and have a high survival rate when stored at 4°C for a long period of time. The outputs of this study confirm the potential of prepared and tested probiotic fish mixtures for future use in in vivo experiments and in fish farms for the prevention of infectious diseases.